Representações sociais de professores sobre alunos adolescentes: um estudo na escola Sagrada Esperança da cidade de Cabinda - Angola - Celsa Mercia Hinaundipula dos Santos (2015)
This research aims to study the social representations about adolescent students made by elementary school teachers at a school in Cabinda, Angola. It is based on the theory of Social Representation by Serge Moscovici, which states that social representation holds the power to organize, unify and filter what will be reintroduced and re-apprehended in the realm of peoples experiences and behaviors along everyday life. Moscovici (1961) established the social representation as a persons construction with social origin and social destination. In this research, we can see that the development of social representations arises from a phenomenon of interaction, because they are built in and by the relationship between teachers and students. Therefore, this is the interest in knowing how these representations are carried out by teachers that work with adolescent students and analyze how they think, feel and act in the relationship with their students. Then, working with these representations, we can find the teachers disposition when they analyze the process of social interaction between themselves and their students. Five people participated in the study and these were the tools used: a questionnaire, a semi-structured interview and an essay on the theme "Adolescence." The data analysis showed that teachers social representations about teenagers students arise from three types of knowledge: traditional knowledge, academic background and the context named by these teachers as street knowledge", which is the knowledge learned in daily social interactions. The representations related to traditional knowledge highlight a son who turns into a man or a daughter who becomes a woman, without specifying any extended time for this transformation. A second group of representations is related to the academic background acquired from teacher training courses or from books. In this second group, we find the representations of adolescence as a difficult and hectic phase as well as a good period, due to the fact that in this period of time, the individual is more receptive and able to better assimilate what is to be learned. The experience itself and the interactions that occur in everyday life are also identified by teachers as a source on their knowledge on adolescent students. Finally, it was possible to link these representations to pedagogical practices developed by these teachers.